A geometrically decoupled, twisted solenoid single‐axis gradient coil set for TRASE. Issue 4 (25th September 2019) - Sun, Hongwei; AlZubaidi, Abbas; Purchase, Aaron; Sharp, Jonathan C.
Abstract : Purpose: TRASE uses phase gradients in the RF transmit field to encode MRI data. A highly efficient twisted solenoid coil was proposed recently for TRASE imaging for transverse B 0 geometries. This novel coil can be rotated to generate a phase gradient in any transverse direction, therefore, combining two such coils would double k‐space coverage for single‐axis encoding, resulting in higher spatial resolution. However, the strong inductive coupling between a pair of coaxial twisted solenoids must be overcome. Methods: Here, we demonstrate that two concentric twisted solenoids, designed using previously described Biot‐Savart calculations, can be geometrically decoupled by attaching to each a regular solenoid in series. The regular solenoid geometry resulting in minimization of mutual inductance was determined from simulations using the FastHenry 2 tool. The effects on TRASE encoding performance due to the regular solenoids were assessed from simulations and experiments. Results: The maximum resulting B 1 magnitude and phase distortions were 3.7% and 4 . 6 ∘, while a good isolation S 12 = - 17.5 dB between the coil pair was obtained. TRASE experiments confirmed the double k‐space coverage, and achieved a rapid spin echo train with 128 k‐space points collected within 80 ms, allowing short T 2 samples to be accurately imaged. Conclusions: This study demonstrates that a pair of twisted solenoid phase gradient RF coils can be geometrically decoupled. Advantages over active PIN diode decoupling include faster switching, lower hardware complexity, and scalability.